Deep Brain Stimulation for the Treatment of Tremor and Ataxia Associated with Abetalipoproteinemia. (2nd July 2012) - Mammis, Antonios; Pourfar, Michael; Feigin, Andrew; Mogilner, Alon Y.
Background: Abetalipoproteinemia is a rare disorder of fat absorption, characterized by vitamin deficiency, acanthocytosis, and neurologic symptoms including ataxia and tremor. Case Report: A 41-year-old male with abetalipoproteinemia is presented. He underwent staged bilateral thalamic deep brain stimulation (DBS) for the treatment of his tremors. After DBS, the patient achieved significant improvements in his tremors, ataxia, and quality of life. Discussion: Thalamic DBS proved to be both safe and efficacious in the management of ataxia and tremors in a patient with abetalipoproteinemia. This is the first report of DBS in abetalipoproteinemia in the literature.